ENT530 : Business Model Convas: Sleepillow Aroma. Co / Muhammad Amiruddin Mohd Kamari ... [et al.] - Mohd Kamari, Muhammad Amiruddin; Mohd Noor, Nurul Jannah; Rosli, Nur Fatihah; Kamarudin, Nursaffaren; Mohd Asri, Nurul Anis Amila (2021)
The overview of this Business Model Canvas (BMC) is that we were able to gain a lot of new knowledge and information about the business and entrepreneurship worlds. This business is focus on partnership enterprise. We started this business to provide high-quality products to our customers while also reducing the burden or problems they face, such as back pain, headaches, stiffness, and insomnia. Our business, aromatic gel pillow, has grown significantly since its inception, and today Sleepillow Aroma. Co offers a variety of aromatic gel pillow designs to our valued customers. As we all know, there are numerous other businesses or companies that sell cool gel pillows these days. As a result, we decided to start-up this business and continue to improve our product in order to meet the needs of our customers and generate more profit and revenue. We chose to start our business because there is a high demand from customers, particularly in Malaysia, because when the temperatures rise, they will require this type of product to solve all of their sweaty night-time problems. We were also success to analyse several aspects of our business using this Business Model Canvas, including our customer relationships and target customer demographic trends. The Business Model Canvas is important in business because it helps us visualize what is important and forces consumers to address key areas, and in fact, we can enhance our product on a regular basis.